Discrepancies between medical oncologists and surgeons in assessment of resectability and indication for chemotherapy in patients with colorectal liver metastases. (20th February 2014) - Homayounfar, K; Bleckmann, A; Helms, H-J; Lordick, F; Rüschoff, J; Conradi, L-C; Sprenger, T; Ghadimi, M; Liersch, T
Abstract: Background: Multidisciplinary discussion of the treatment of patients with colorectal liver metastases (CRLM) is advocated currently. The aim of this study was to investigate medical oncologists' and surgeons' assessment of resectability and indication for chemotherapy, and the effect of an educational intervention on such assessment. Methods: Medical histories of 30 patients with CRLM were presented to ten experienced medical oncologists and 11 surgeons at an initial virtual tumour board meeting (TB1). Treatment recommendations were obtained from each participant by voting for standardized answers. Following lectures on the potential of chemotherapy and surgery, assessment was repeated at a second virtual tumour board meeting (TB2), using the same patients and participants. Results: Overall, 630 answers (21 × 30) were obtained per tumour board meeting. At TB1, resectability was expected more frequently by surgeons. Participants changed 56·8 per cent of their individual answers at TB2. Assessment shifted from potentially resectable to resectable CRLM in 81 of 161 and from unresectable to (potentially) resectable CRLM in 29 of 36 answers. Preoperative chemotherapy was indicated more often by medical oncologists, and overall was included in 260 answers (41·3 per cent) at TB1, compared with only 171 answers (27·1 per cent) at TB2. Medical oncologists more often changed their decision to primary resection in resectable patients ( P = 0·006). Postoperative chemotherapy was included in 51·9 and 52·4 per cent of all answers at TB1 and TB2 respectively, with no difference in changes between medical oncologists and surgeons ( P = 0·980). Conclusion: Resectability and indication for preoperative chemotherapy were assessed differently by medical oncologists and surgeons. The educational intervention resulted in more patients deemed resectable by both oncologists and surgeons, and less frequent indication for chemotherapy. Abstract : Judgement of resectability differs substantially